The puzzle of linguistic variation: a grammatical maze for studying gender processing in two diatopic varieties of Spanish - Stetie, Noelia Ayelén; Tzinavos Muñoz, Sofía María; Tomé Cornejo, Carmela; Zunino, Gabriela Mariel (Frontiers in Language Sciences, 2026)
Recent advances in psycholinguistics have increasingly recognized the importance of linguistic variation as central to understanding language processing. Gender represents an interesting area for analysis, as it allows us to observe the interactions between linguistic and socio-cultural phenomena during language processing. Particularly, Spanish is a paradigmatic language for studying this phenomenon, as it features grammatical gender and exhibits documented diatopic differences in its use and conceptualization. We seek to examine: (a) the impact of different types of information related to gender (grammatical vs. stereotypical) and (b) potential differences within Spanish-speaking communities. We conducted a G(rammatical)-maze task in which we considered three independent variables: grammatical gender, stereotypical (gender) bias and linguistic community. We manipulated two independent variables with two levels each to design the experimental items: stereotypical bias of the role nouns (female, male), grammatical gender (feminine, masculine). The task involved 277 Spanish speakers from Argentina (N = 143) and Spain (N = 134). Our results of the G-maze task replicate the documented (in)congruence pattern reported in prior research: the highest processing cost appears in the condition with male-biased role nouns with feminine morphology (herreras, female blacksmith). This indicates an asymmetry in the gender incongruence effect: the incongruence is more prominent in the case of male-biased role nouns with feminine morphology. As an unexpected finding, our results show a significant difference in the pronoun processing between the two Spanish diatopic varieties. We pose some possible interpretations due to syntactic and semantic factors, however it would be necessary to test it with an experiment specifically designed for that purpose. Finally, due to the results of some previous studies, we analyzed potential differences conditioned by gender identity. We found that, for both communities, men show a stronger asymmetric incongruence effect. This pattern could be interpreted as a greater difficulty for men to represent women in stereotypically male roles, such as camioneras (female truck drivers). Taken as a whole, our results highlight the value of psycholinguistic approaches to intra-linguistic variation, particularly in understanding how linguistic and sociocultural factors influence real-time comprehension across diatopic varieties.